The Bull of Phalaris and the Historical Method of Diodorus of Sicily - Dudzinski, Andrzej (Histos, 2013)
The problems surrounding the bull of Phalaris have exercised ancient historians for well over a century now. The present study aims to open a new perspective in dealing with these problems by questioning the key assumptions that underlay earlier explanations—and which still, indeed, underlie some recent discussions: namely, that the scholiast on Pindar, Pyth. 1.185 (95) transmits Timaeus more accurately than do the historians Polybius and Diodorus, and that Timaeus himself was right in his original claims, whatever exactly they were. From this new perspective, Polybius’ observations concerning the authenticity of the bull from Carthage should be accepted; both Polybius’ and Diodorus’ versions of what Timaeus wrote emerge as more trustworthy than the scholiast’s; the faulty logic of the scholiast’s account is explained by its origins; Timaeus’ errors are exposed; and a convincing biography of the bull can be reconstructed. Diodorus’ historical methods concerning these problems are also re-evaluated in the light of recent rehabilitation of his work. His discussion of Phalaris’ bull does not provide evidence of lack of intellect, carelessness or slavish reliance on sources, but on the contrary shows that he interrogated his sources and responded both to the demands and the necessary limitations of his particular type of historiography.